High order vector mode coupling mechanism based on mode matching method. (2nd May 2017) - Zhang, Zhishen; Gan, Jiulin; Heng, Xiaobo; Li, Muqiao; Li, Jiong; Xu, Shanhui; Yang, Zhongmin
Abstract: The high order vector mode (HOVM) coupling mechanism is investigated based on the mode matching method (MMM). In the case of strong HOVM coupling where the weakly guiding approximation fails, conventional coupling analysis methods become invalid due to the asynchronous coupling feature of the horizontal and vertical polarization components of HOVM. The MMM, which uses the interference of the local eigenmodes instead of the assumptive modes to simulate the light propagation, is adopted as a more efficient analysis method for investigating HOVM coupling processes, especially for strong coupling situations. The rules of the optimal coupling length, coupling efficiency, and mode purity in microfiber directional coupler are firstly quantitatively analyzed and summarized. Different from the specific input modes, some special new modes would be excited at the output through the strong HOVM coupling process. The analysis of HOVM coupling mechanism based on MMM could provide precise and accurate design guidance for HOVM directional coupler and mode converter, which are believed to be fundamental devices for multi-mode communication applications.